The effectiveness of state measures of financial support for businesses during COVID-19 on the example of the "Economy of Simple Things" program - Rakhymzhan, U. (M. Marikbayev KAZGUU University International School of Economics, 2023)
This research examines the effectiveness of the "Economy of Simple Things" program in Kazakhstan, which is aimed at providing financial assistance to business entities affected by the COVID-19 pandemic. Using a quantitative approach, this study analyzes the impact of the program on key economic indicators, such as lending, employment, wages, etc. It also examines the distribution of funds within the program and evaluates the achievement of the intended goals. The results show that the program faced bureaucratic obstacles and long processing times. The program itself did not have a significant impact on employment and wage growth, since the wage increase was due to other factors. Moreover, the program had a limited impact on food prices, which continued to rise. The analysis reveals program's limitations, including issues with the funding situation and the selection process. Overall, this study provides valuable information on the effectiveness of government financial support measures for businesses during the COVID-19 crisis, emphasizing the importance of targeted and well-thought-out policies to ensure the survival and growth of this vital sector of the economy.
Keywords: Economy of Simple Things; Government support programs; COVID-19 pandemic; Business financing; Employment and wages; Economic policy effectiveness; Kazakhstan